Murine Models of Lysosomal Storage Diseases Exhibit Differences in Brain Protein Aggregation and Neuroinflammation - Jennifer Clarke; Can Kayatekin; Catherine Viel; Lamya Shihabuddin; Sergio Pablo Sardi (Biomedicines, 2021)
Genetic, epidemiological and experimental evidence implicate lysosomal dysfunction in Parkinson’s disease (PD) and related synucleinopathies. Investigate several mouse models of lysosomal storage diseases (LSDs) and evaluate pathologies reminiscent of synucleinopathies. We obtained brain tissue from symptomatic mouse models of Gaucher, Fabry, Sandhoff, Niemann–Pick A (NPA), Hurler, Pompe and Niemann–Pick C (NPC) diseases and assessed for the presence of Lewy body-like pathology (proteinase K-resistant α-synuclein and tau aggregates) and neuroinflammation (microglial Iba1 and astrocytic GFAP) by immunofluorescence. All seven LSD models exhibited evidence of proteinopathy and/or inflammation in the central nervous system (CNS). However, these phenotypes were divergent. Gaucher and Fabry mouse models displayed proteinase K-resistant α-synuclein and tau aggregates but no neuroinflammation; whereas Sandhoff, NPA and NPC showed marked neuroinflammation and no overt proteinopathy. Pompe disease animals uniquely displayed widespread distribution of tau aggregates accompanied by moderate microglial activation. Hurler mice also demonstrated proteinopathy and microglial activation. The present study demonstrated additional links between LSDs and pathogenic phenotypes that are hallmarks of synucleinopathies. The data suggest that lysosomal dysregulation can contribute to brain region-specific protein aggregation and induce widespread neuroinflammation in the brain. However, only a few LSD models examined exhibited phenotypes consistent with synucleinopathies. While no model can recapitulate the complexity of PD, they can enable the study of specific pathways and mechanisms contributing to disease pathophysiology. The present study provides evidence that there are existing, previously unutilized mouse models that can be employed to study pathogenic mechanisms and gain insights into potential PD subtypes, helping to determine if they are amenable to pathway-specific therapeutic interventions.